Asuhan Kebidanan Komprehensif pada Ny. A Umur 26 Tahun dengan Kekurangan Energi Kronik dan Riwayat Tuberculosis di Puskesmas Paguyangan - Iqlima Fristy Wahrolis; Maryam Maryam; Widi Astuti (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
According to the World Health Organization (WHO), in 2023, around 305,000 per 100,000 live births of women will die due to prevalence due to CED related to pregnancy throughout the world, MMR in ASEAN in 2023 will be 100 per 100,000 live births with prevalence due to CED 40%, MMR in Indonesia in 2023 will be 4,129 with a prevalence due to KEK of 17.3%, MMR in Central Java will be 183 per live birth with a prevalence due to KEK of 6.7%. The MMR in Brebes is 1,083 with a prevalence due to CED of 5%, in Paguyangan women with a prevalence of CED from 2023-2024 is 119 cases. To find out about cases of pregnancy, childbirth, childbirth, postpartum and birth control Mrs. A with CED and history of TB. Qualitative descriptive research method with a case study approach. Comprehensive Care for Mrs. A was found to have problems with pregnancy with CED and a history of TB. Childbirth was carried out by induction based on KPD indications, there were no problems or abnormalities in the postpartum period, the postpartum period was still CED and had mild anemia, there were no complications during the postpartum period. Mrs. A chose the KB implant and there were no complaints after installation. It can be concluded that comprehensive midwifery care for Mrs. At 26 years of pregnancy, childbirth and postpartum there is a gap between theory and practice.